Developing Website as Media in Wordpress Assisted in Learning Momentum, Impulse, and Collision to Improve Students' Creative Thinking Skills - Mansur Solaiman; Heru Kuswanto; Insih Wilujeng (Jurnal Penelitian Pendidikan IPA, 2024)
Teachers are expected to have several competences; master teaching materials and have Indonesian character and personality, inspire and be a role model, have a charming appearance, be authoritative, firm, sincere, and disciplined who are able to educate, learn, guide, direct, train, assess, and evaluate students in accordance with the demands of current and future developments in information and communication technology. The purpose of this research is to develop a word press-based website to improve students' creative thinking skills in the physics concept of impulse and impact momentum. The method used in this research is development research or Research and Development (R&D) with the ADDIE model including five stages, namely the Analyze, Design, Development, Implementation, and Evaluate stages. The results showed that the wordpress-based website media developed was feasible to use for learning momentum, impuils and collisions on MA Ali Maksum students in class X physics subjects with a value of 86.3% media attractiveness aspect, 87.0% material adequacy and 83.7% language use and media validity declared feasible, and wordpres-based website learning media can also improve students' creative thinking skills on the concept of momentum, impulse and collision.